(untitled) (The Pakistan Development Review, 2007)
In Pakistan agriculture land accounts for a large portion of total wealth and the distribution of this land effects household welfare and agriculture efficiency. Evidence shows that in developing countries, land inequality is detrimental to overall efficiency due to incomplete markets and therefore results in welfare losses to those with little or no land as there are several benefits associated with access to land [Vollrath (2007)]. Agriculture plays a pivotal role in the economy of Pakistan which contribute 22.4 percent to Gross Domestic Product, 43.05 percent of labour force engaged in agriculture sector and 67 percent of population reside in rural areas out of which 30 percent of people living below the official poverty line. As the climate of Pakistan is arid to semi arid, its 80 percent agriculture is irrigated. Pakistan has one of the largest irrigation system in the world based on Indus basin irrigation system which plays an important role in the development of agriculture and the nature of distribution of irrigation water across farm size groups determines to a significant extent the nature of distribution of agriculture income.